2004
DOI: 10.1038/sj.bjc.6601882
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic-based identification of haptoglobin-1 precursor as a novel circulating biomarker of ovarian cancer

Abstract: Screening for specific biomarkers of early-stage detection of ovarian cancer is a major health priority due to the asymptomatic nature and poor survival characteristic of the disease. We utilised two-dimensional gel electrophoresis (2DE) to identify differentially expressed proteins in the serum of ovarian cancer patients that may be useful as biomarkers of this disease. In this study, 38 ovarian cancer patients at different pathological grades (grade 1 (n ¼ 6), grade 2 (n ¼ 8) and grade 3 (n ¼ 24)) were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 29 publications
7
91
0
Order By: Relevance
“…ApoA-IV is a 46 kD plasma glycoprotein with limited associations with cancer; Kawakami and colleagues showed ApoA-IV to increase in sera from hepatocellular cancer after radiofrequency ablation [20]. HP is a well characterized APP with increasing evidence as a cancer biomarker [21][22][23][24][25]. Lastly, SAA is an acute phase apolipoprotein associated as a marker of cancer progression [26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…ApoA-IV is a 46 kD plasma glycoprotein with limited associations with cancer; Kawakami and colleagues showed ApoA-IV to increase in sera from hepatocellular cancer after radiofrequency ablation [20]. HP is a well characterized APP with increasing evidence as a cancer biomarker [21][22][23][24][25]. Lastly, SAA is an acute phase apolipoprotein associated as a marker of cancer progression [26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, some of the identified biomarkers in our study were found to be modulated by various cancer diseases in other serum-based proteomic studies. Thus, haptoglobin was found upregulated in serum of ovarian, oesophageal and small-cell lung cancer patients (Steel et al, 2003;Ahmed et al, 2004;Bharti et al, 2004), while complement C3 and apolipoprotein A1 (Steel et al, 2003;Zhang et al, 2004) were found downmodulated in liver or ovarian cancer. However, these studies were dedicated to the identification of serum biomarkers associated to cancer diagnosis, rather than prediction of clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of them may yet potentially directly impact on the metastatic process. For example, haptoglobin, an acutephase protein mainly produced in the liver has been shown to be upregulated in the serum of patients with various solid tumors (Ahmed et al, 2004;Bharti et al, 2004;Kwak et al, 2004;Tolson et al, 2004), and has also been demonstrated to participate in angiogenesis, tissue remodeling and cell migration (Cid et al, 1993;De Kleijn et al, 2002). Similarly, a proposed role for transferrin signalling has been suggested in regulating the metastatic capacity of various solid tumors including breast cancer (Nicolson et al, 1992;Inoue et al, 1993;Cavanaugh and Nicolson, 1998;Cavanaugh et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that at least three structurally different protein species can be differentiated and accounted for the most commonly observed spot patterns of haptoglobin a chains. As shown in Table 2, haptoglobin has been shown to be a potential marker of cancer [37][38][39]. Watanabe et al [40], after having analyzed serum samples from pregnant women by 2-DE, were able to identify in women presenting with preeclampsia a group of overexpressed spots corresponding to clusterin.…”
Section: Clinical Applications -Biomarker Identificationmentioning
confidence: 99%